Pengembangan Usaha Keramba Jaring Apung (KJA) Ikan Kerapu Cantang pada Kelompok Pembudidaya Kuala Cangkoi - Zulfahmi, Ilham; Perdana, Adli Waliul; Rianjuanda, Rianjuanda; Akmal, Yusrizal; Nafis, Badratus (Jurnal SOLMA, 2023)
Background: Cantang grouper farmed by kuala cangkoi fish farming group, Banda Aceh shows growth delay due to lack of knowledge and skills related to water quality management and feed production. This service activity aims to develop the cantang grouper farming business in the Kuala Cangkoi fish farming group through the application of water quality management science and technology, science and technology related to feed production, and science and technology related to bookkeeping and marketing. Methods: The stages of service are in the form of cage preparation, socialization and supervision, training and assistance in water quality management, training and assistance in feed production, as well as training and assistance in bookkeeping and marketing to partner groups. Evaluation and success of activities are reviewed through questionnaires in the pre-activity and post-activity sections. Results: The knowledge and skills of partner group members who were able to measure water quality increased to 87% (understanding and very understanding) from 60% previously. The knowledge and skills of partner group members who understand and are very savvy in producing feed increased to 87% from only 57% previously. Meanwhile, the percentage of partner group members who were able to understand online bookkeeping and marketing techniques increased to 87% from 34% previously. Conclusion: improve the knowledge and skills of partners, especially in the field of water quality management and artificial feed production which has an impact on increasing the survival and growth of cantang grouper farmed in floating net cages.